Acculturative Stress, Psychological Adjustment and Future Orientation Among International Students in Turkey - Temircan, Zekeriya (My University, 2022)
The aim of this study was to examine the relationship between acculturative stress, psychological adjustment, and future orientation among international students in Turkey. 650 students were included in this research and the participants completed Acculturative Stress Scale for International Students (ASSIS), The College Adjustment Scale (CAS) and future Orientation Questionnaire. Data were analyzed by using the SPSS 25.0 statistics program. Results indicated that a positive correlation was found between acculturative stress, psychological adjustment, and future orientation. The analysis showed that gender differences in psychological adjustment showed statistical significance among the students. Also, female students reported higher scores on acculturative stress than male students and they are more prone to homesickness, fear and interpersonal problems. The findings emphasize the potential role of psychological adjustment in relation to future orientation. The necessary steps need to be taken to prevent acculturative stress factors for students. Interventions by universities, authorities and other stakeholders should help prepare students socially and psychologically in the host culture for their future endeavors.
Keywords: International Students; Acculturative Stress; Psychological Adjustment; Future Orientation